Transferability of microssatellite markers to Trichogramma pretiosum Riley, 1879 (Hymenoptera: Trichogrammatidae) - Araújo Júnior , Luis Moreira de; Zago, Hugo Bolsoni; Ferreira, Marcia Flores da Silva; Pratissoli, Dirceu; Pereira, Aléxia Gonçalves; Damascena, Alixelhe Pacheco (Revista de Ciências Agroveterinárias, 2022)
The biological pest control has expanded in Brazil with the Trichogramma pretiosum as the main natural enemy. The microsatellite molecular markers Simple Sequence Repeat (SSR) have been the most used, as they are multiallelic, robust and reproducible, in several species. In order to optimize future processes of identification and analysis of the parasitoid's genetic diversity, twenty markers, isolated and characterized for the parasitoid wasp Trichogramma dendrolimi, were tested in 15 generations of T. pretiosum. Those markers, ten have been transferred and can be used to evaluate the genetic variation of T. pretiosum.